La mise en oeuvre judiciaire de l'article 1 de la Charte canadienne et le droit de la preuve - Binette, André (Les Cahiers de droit, 1986)
The object of this paper is to show that rules of evidence are often unworkable in s. 1 Canadian Charter cases. A survey reveals that courts tend to use these rules selectively when a party attempts to demonstrably justify a reasonable limit to a guaranteed right or freedom. A parallel is made with the Supreme Court of Canada's flexibility in admitting extrinsic material in constitutional references. American law is useful in that it establishes the key distinction between adjudicative facts and legislative facts. Rules of evidence apply only to the former category. Legislative facts correspond to facts needed for a s. 1 demonstration. It should be recognized in Canada that rules of evidence are inapplicable to such facts because of the specific purpose and importance of judicial reasoning in Charter cases.